PENCAPAIAN KEMAMPUAN SAINS SISWA PADA KONSEP PESAWAT SEDERHANA MELALUI ASESMEN ISOMORFIK - Sudarto Sudarto; Abdul Kadir; Andi Nurviviani (Jurnal Inovasi Penelitian, 2023)
This research is a pre-experimental research which aims to determine the achievement of students' abilities in the concept of simple airplanes through the application of Isomorphic Assessment in the 5th Grade of SD Inpres 3/77 Pasaka. The population in this study were all the fifth grade students at SD Inpres 3/77 Pasaka, in totaling of 17 students. Sampling using nonproblality sampling technique. The data collection technique used is the provision of test sheets. The data analysis technique is descriptive analysis and. The results obtained in this research were: the number of students (respondents) who got a score in the "very good" category were 6 people or 41.16% of students and those who got the "good" category were 11 people or 58.8% of students. Conclusion : generally the students obtain the science abilities in the "good" category, which means that giving the qualitative-qualitative Isomorphic Test enables students to achieve maximum science abilities, especially in the simple airplane concepts